Micronized natural talc affects the proteins and pectic cell wall polysaccharides during "Hojiblanca" virgin olive oil extraction. Issue 1 (19th July 2016) - Sadkaoui, Abir; Jiménez, Antonio; Pacheco, Rafael; Beltrán, Gabriel
Abstract : This work studies how using MNT affects cell wall polysaccharides and proteins of "Hojiblanca" paste during virgin olive oil extraction. Four doses of MNT were assessed: 0, 0.25, 0.5, and 1%. Three pectic fractions were extracted from alcohol insoluble solids (AIS): water‐soluble pectin (WSP), chelate‐soluble pectin (CSP), and non‐soluble pectin (NSP). In general, the content of the three pectic fractions decreased throughout the kneading step. This indicated a significant degradation and solubilization of pectins during processing. The same trend was observed for protein content and total pectin content while AIS yield increased. Addition of MNT at doses lower than 0.5% favored the formation of a chemical bound through electrostatic interactions between proteins and pectic polysaccharides which are held together and adsorbed onto the talc surface giving a decrease in their content. Higher MNT doses (1%) produced the opposite behavior. The lowest dose of MNT (0.25%) reduced the oil losses in the pomace. A certain tendency for the loss of oil in the pomace to decrease as the amount of total pectin and protein decreased was observed, indicating that the oil yield is at least in part, related to the pectin and protein content depending on the dose of MNT added during malaxation step. Practical application: We have demonstrated that the use of talc during the malaxation step greatly lessens the effect of the pectic substrates and proteins, principal emulsifier agents that influence the formation of oil‐in‐water emulsions during oil extraction process and enhance the extraction of the oil from the mesocarp cells by reducing its loose in the pomace. Excess of talk addition presented a reverse effect, though. It is, therefore, of the utmost importance that the information contained in this study is fully taken into account to establish the suitable dose of talc that should be applied when difficult pastes are formed during malaxation step and which at least partially depends on the content of proteins and pectin compounds of the processed olive paste. Proteins and pectic cell wall polysaccharides as affected by talc addition during virgin olive oil extraction. Abstract : Proteins and pectic cell wall polysaccharides as affected by talc addition during virgin olive oil extraction.